COVERAGE OF THE KORBOSHI MOVEMENT ABROAD - Abdukamolova Mohlaroy Shuxratjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The modern history of Uzbekistan is a captivating tale of a nation that has experienced remarkable transformation and transition since gaining independence in 1991. Situated in Central Asia, Uzbekistan holds a rich historical legacy that stretches back centuries, blending influences from the Silk Road, various empires, and cultural exchanges. In this article, there are given main information about coverage of the Korboshi movement abroad.